The status of Crossopalpus obscuripes (Adams), a new junior synonym of Crossopalpus aenescens (Wiedemann) (Diptera: Hybotidae: Tachydromiinae) - Cumming, Jeffrey M.; Sinclair, Bradley J. (Zootaxa, 2014)
Adams (1905) described a new species, Stilpon obscuripes, from two female specimens collected near Salisbury, Rhodesia (now Harare, Zimbabwe) by Frank L. Snow. Although Smith (1969) briefly treated this species under the genus Stilpon Loew in his monograph on the Empididae of southern Africa, it is evident that he had not seen the type material. The species remained little known until Cumming & Cooper (1992) examined the syntypes and transferred the species to Crossopalpus Bigot, indicating that C. obscuripes (Adams) was allied to C. aenescens (Wiedemann). During preparation of the Hybotidae chapter for the Manual of Afrotropical Diptera (Sinclair & Cumming, accepted), C. obscuripes was re-examined and discovered to be identical to C. aenescens, which was originally described from South Africa. The Crossopalpus aenescens-group was previously studied by Collin (1960), who recognized four included species, and Smith (1967), who provided a key to the species and illustrations of the male terminalia (i.e., right surstylus) of this complex.